Paradigma Teori Belajar Konstruktivisme Vygotsky pada Pembelajaran Abad-21 serta Relevansinya dengan Kurikulum Merdeka Sekolah Dasar - Zakariyah, Yogi Aldias; Puspita, Intan Dia; Buaga, Garib Firman; Windy, Windy (Faculty of Teacher Training and Education, Musamus University, 2022)
21st century learning are fundamental in developing aspects of learning in the world of education in Indonesia. The purpose of this research is to analyze and explain the relevance of Vygotsky's constructivism learning theory in the independent curriculum in elementary schools. 21st century learning in the independent curriculum in differentiated learning is an effort to adjust the learning process in the classroom with the aim of meeting the learning needs of each individual. The adjustment is by developing learners' 4C abilities, interests, learning profiles and learners' readiness in order to achieve improved learning outcomes. Learners can learn according to their own abilities and find understanding from their own experiences. This research was used the library research method by analyzing related literature sources and articles and books as references. Vygotsky's constructivism emphasizes the interaction of interpersonal (social), cultural-historical, and individual factors as the key to human development. Constructivism theory has relevance to differentiated learning in terms of meaningful learning and learner engagement. The results of 21st century learning in the independent curriculum in differentiated learning apply the theory of constructivism in learning by paying attention to the individual characteristics of students. Supported by the concept of Zone of Proximal of Development (ZPD) and scaffolding is very relevant in differentiated learning that accommodates all the potential of students and pays attention to the individual abilities of students so that they can optimize the 4C skills of students.